Formation mechanism of faulted bands and its effect on α′-martensitic transformation. (December 2022) - Xi, Xiaohui; Dong, Guangqi; Wang, Lingyu; Hu, Jun; Shen, Chunguang; Wang, Jinliang; Xu, Wei
Graphical abstract: Highlights: Apart from deformation-induced shear bands, the similar bands can be also formed under cryogenic treatment and exist as micro-twin, thin ε-martensite and faulted austenite. In this work, it was defined as faulted band. Faulted bands were firstly nucleated at grain boundary and twin boundary, and then grew into the grain interior as linear morphology. The start formation temperature was higher than martensitic transformation start (Ms ) temperature. Faulted bands can provide nucleation sites for martensitic transformation and promote martensitic transformation. Meanwhile, the faulted bands can effectively impede the growth of martensite lath. Also, the variant types of faulted bands determined the variant types of martensitic packets. The research on the effect of morphology and structure of faulted bands on martensitic transformation further revealed that a close correlation was found between thermal and mechanical stability of austenite. Abstract: Understanding the martensitic transformation mechanism is of critical importance to control martensitic transformations and hence retained austenite. Linear defects reported in a previous study can provide nucleation sites for martensitic transformation, but their nature, formation mechanism and effect on martensitic transformation were not revealed. In this study, detailed evidence was provided that linear defects were formed by the motion of Shockley partial dislocation on a close-packed plane and usually could be in the form of faulted austenite, twins and ɛ-martensite, defined as faulted bands. Faulted bands were formed prior to martensitic transformation at a starting transition temperature higher than Ms . They can provide nucleation sites for α′-martensitic transformation but can act as an effective barrier to limit the growth of α′-martensite laths. In addition, the same plane was found between the formation plane of the faulted band and the habit plane of α′-martensite, which indicates that the variant types of α′-martensite were decided by the variant types of faulted bands.